Echocardiographic Diagnosis and Hemodynamic Evaluation of Patent Ductus Arteriosus in Extremely Low Gestational Age Newborn (ELGAN) Infants - Singh, Yogen; Fraisse, Alain; Erdeve, Omer; Atasay, Begum (Frontiers in Pediatrics, 2020)
Persistent Patent ductus arteriosus (PDA) is a common finding in extremely low gestational age newborn infants and its prevalence is inversely proportional to the gestational age. The presence of a persistent PDA is associated with increased mortality and several significant morbidities including intraventricular hemorrhage, pulmonary hemorrhage, necrotizing enterocolitis and chronic lung disease or bronchopulmonary dysplasia. However, treating PDA has not been demonstrated to have beneficial impact on the long term outcomes. Currently there is no consensus on whether to treat the PDA or not, and if treat, when to treat and how to treat. The echocardiography is the investigation of choice to diagnose PDA, estimating the magnitude of shunt volume and assessing its hemodynamic significance, and to exclude/diagnose any associated congenital heart defect before any intervention. Various echocardiographic parameters and staging / scoring systems have been described to help the clincians making the clinical decisions and some of theses scoring systems are quite complex to apply in a busy day to day clinical practice. This concised review paper is focused to help the clinicians in making a clinical decision based upon clincial and echocardiography parameters. Hence, only the parameters which are commonly used and helpful in making the clinical decisions in day to day clincial practice have been described in this paper.